2018
DOI: 10.1016/j.chieco.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Where are the migrants from? Inter- vs. intra-provincial rural-urban migration in China

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 34 publications
6
71
0
Order By: Relevance
“…Engaging in agricultural production and enrollment in health insurance elsewhere indicate ties to rural origins. Since permanent or long-term migrants tend to migrate within the provincial borders [55,56], the proportion of intraprovincial migrants in a household can be important. Households that are split in different locations are less likely to commit to settling down, so a binary variable was used to indicate split households.…”
Section: Methodsmentioning
confidence: 99%
“…Engaging in agricultural production and enrollment in health insurance elsewhere indicate ties to rural origins. Since permanent or long-term migrants tend to migrate within the provincial borders [55,56], the proportion of intraprovincial migrants in a household can be important. Households that are split in different locations are less likely to commit to settling down, so a binary variable was used to indicate split households.…”
Section: Methodsmentioning
confidence: 99%
“…With the frequent flow of population in the regions, it is necessary to study the impact of population mobility on urbanization convergence. Su et al (2018) and Chen et al (2019) believed that population mobility has a significant impact on the structure and trends of regional differences. Population mobility increases inter-regional development differences and aggravates the phenomenon of "border effect".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have also suggested negative health well-being consequences from rural-to-urban migration for migrants themselves [31], and to the elderly and children left behind in the rural areas [32,33]. The decision and determinants of rural-to-urban migration also concern many scholars [34,35]. Although previous research has generated an impressive body of work, most of the existing studies explore the social issues that are caused by RUMs.…”
Section: Introductionmentioning
confidence: 97%